Analisis Kemampuan Berpikir Kritis Matematis Siswa Kelas VIII Melalui Pendekatan Open- Ended - Rika Putri; Eka Khairani Hasibuan (Universitas Asahan, 2023)
In general, mathematics learning is monotonous, as a result the teaching process is teacher-centered, so students are less active in learning mathematics. So, a mathematical approach is needed, namely the Open-Ended approach. This research is a descriptive research with a qualitative approach. The subjects of this study were 30 students of grade VIII – A MTs Darul Irsyadiyah. Through the results of the Open-ended question test, the SPLDV material given to students of grade VIII-A MTs Darul Irsyadiyah amounted to 30 students obtained by students with critical thinking level group 4 (TBK 4) with a percentage of 10%, students of critical thinking level 3 (TBK 3) percentage of 13%, students of critical thinking level group 1 (TBK 1) with a percentage of 14%. Based on the results of interviews with open-ended syntax conducted on each group of TBK, it was concluded that students of grade VIII-A MTs Darul Irsyadiyah were only able to think critically on two or three indicators, this showed that students were not fully developed to develop critical thinking skills in solving open-ended problems of the Two Variable Linear Equation System (SPLDV) material.